Heterotopias, experiências migratórias e arranjos disposicionais de cubanos no Canadá - Elisa Beatriz Ramirez Hernandez (2023)
This research addresses spatial and temporal relations, communicational practices, transnational and diasporic links in the ways of life of Cuban immigrants in Canada (Montreal). The aim is to understand how these migrants create the spaces and times that communicationally configure their migratory experiences, from narrations, conversations, encounters, interaction environments, gambiarras and arrangements in the conditions of existence in difference. For this, we address the possible dialogues between ethnographically inspired methodological approaches and a theoretical framework guided by a reflection on the notions of heterotopia, experience, and dispositif, fundamentally from a Foucauldian perspective. From extended fieldwork in the city of Montreal (2019, 2020- 2021, 2022), we explore research spaces that unfold in virtual and physical environments and that conform a communicational interactional dispositif from heterotopic relations. On the one hand, we find a diverse community of migrants from the island who relate through a Cuban restaurant in Montreal. Another group of Cubans who participate in the research, more homogeneous and not part of the restaurant's public, are highly educated immigrants that interact daily through a WhatsApp group of more than 40 members. The Facebook network also constitutes a space to follow the Cubans we meet in this city, either through personal profiles or in a Messenger chat group where younger Cubans who have recently arrived in Montreal interact. Besides the semi-structured interviews conducted with ten participants, the empirical corpus of the research is made up of field observations and interactions, collected digital materials, and other records that also configure the migrants' experience, such as photos, letters, and objects that compose the heterotopic map of this experience. In this sense, we seek to a) describe the Cuban transactional context from the historical and current panorama of Cuban migration, as well as the recent development of ICTs and digital media in the country; b) explore spatial and temporal notions as central categories in migration and communication studies, to develop a theoretical-methodological approach around migratory heterotopias; and c) analyze Cuban migrants' forms of interaction, experiences and spatio-temporal relations through heterotopic places, bodily experiences and transnational media dispositif. These migratory heterotopias arise from places of reunion and crossings, digital spaces of interaction, transnational links, suffering and narrative bodies, the forms of control of these bodies and the gambiarras that allow them to invent other possible lives. This work contributes, fundamentally, to the development of a theoretical and methodological proposal to understand migratory processes and communication practices from these "other spaces", where the difference is revealed as a political gesture that shapes ways of life, ones that are continuously reinvented in the experience of migration. This thesis is, moreover, an attempt at other ways of doing research, sometimes by proposing new arrangements between the researcher and the meeting places with the subjects that accompany her; sometimes by the inevitable risk of bringing the marks of collective, transnational, and perpetual displacement that is to live the research process as heterotopia.